Using Ethno-Compositional Materials for Contemporary Music Composition: 'Ovie' E Flat Alto Saxophone and Piano Accompaniment as Musical Example (Global Journal of Human-Social Science, 2020)
The search for musico-cultural identity and nationalism in Africa as well as in Nigeria gave rise to the evolution of new compositional innovations which stemmed from the use of ethno-compositional materials drawn from such cultures for compositional purposes which are contemporary in structure, culturally oriented and globally relevant. In response to this search, Nigerian Contemporary musicians and Art musicians/composers went back as it were to their 'root' giving birth to many contemporary compositions by various contemporary musicians and art musicians in Nigeria and Afr ica including other cultural clime. One of such contemporary composition is the musical example titled 'Ovie' for E flat Alto Saxophone and Piano accompaniment. In the musicological presentation of 'Ovie' for E flat Alto Saxophone and Piano accompaniment, the melodic structure/passage of the song texts 'ovie' was used as thematic mater ial to compose an entire work of 173 bars/measures. Presentation of information pertaining to its pre-compositional consideration and compositional techniques employed in the composition titled 'ovie' was discussed. Also literatures were reviewed to buttress facts where necessary.
Keywords: ethno; compositional materials; musicocultural.